Population divergence in nutrient-temperature interactions in Pieris rapae - Parker, Anna L.; Kingsolver, Joel G. (Frontiers in Insect Science, 2023)
The interaction between larval host plant quality and temperature can influence short-term physiological rates and life history traits of insect herbivores. These factors can vary locally, resulting in local adaptation in responses to diet and temperature, but comparison of these interactions between populations is infrequently studied. Here we examine how the macronutrient ratio of artificial diet determines larval growth, development and survival of larval Pieris rapae (Lepidoptera: Pieridae) at different temperatures between two invasive North American populations from different climatic regions. We use a fully-factorial experiment with three temperature treatments (18, 25 and 32 °C) and three artificial diet treatments varying in the ratio of protein to carbohydrate (Low Protein, Balanced, and High Protein). The effects of diet on life history traits were greater at lower temperatures, but these differed between populations. Larvae from the subtropical population had reduced survival to pupation on the low protein diet in the cold temperature treatment, whereas larval survival for the temperate population was equally high for all temperature and diet treatments. Overall, both populations performed more poorly (slower rates of consumption, growth, and development, and smaller pupal mass) on the low protein ratio diet, but larvae from the temperate population were less sensitive to diet ratio changes at all temperatures. Our results confirm that the physiological and life history consequences of imbalanced nutrition for insect herbivores may depend on developmental temperatures, and that different geographic populations of P. rapae within N. America vary in their sensitivity to nutritional balance and temperature.